2007
DOI: 10.1111/j.1365-2664.2007.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplementary winter seed food on breeding populations of farmland birds: evidence from two large‐scale experiments

Abstract: Summary1. Low winter food availability is probably critical in the declines of many farmland bird species in Europe, leading to the implementation of ameliorative agri-environment scheme options. To date, however, there has been no experimental test of the effectiveness of such options. 2. We report the results of two large-scale, 3-year, controlled experiments investigating the effects of supplementary winter seed provision on breeding farmland bird abundance. In each experiment, the use of winter feeding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
89
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 34 publications
1
89
0
2
Order By: Relevance
“…Buckingham & Peach 2006, Siriwardena et al 2007. Recent experimental research has also shown that seed-eating birds alter their foraging behaviour in response to vegetation manipulation (Devereux et al 2006, Whittingham et al 2006a) and the perceived predation risk has been suggested as a key factor explaining why granivorous birds prefer areas with greater visibility for foraging and feeding on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Buckingham & Peach 2006, Siriwardena et al 2007. Recent experimental research has also shown that seed-eating birds alter their foraging behaviour in response to vegetation manipulation (Devereux et al 2006, Whittingham et al 2006a) and the perceived predation risk has been suggested as a key factor explaining why granivorous birds prefer areas with greater visibility for foraging and feeding on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…However, while this may explain some of the inconsistent results within species or option categories, the number of significant effects and their consistency in direction indicate that the general patterns in the stubble and WBS results are likely to be robust. Previous research has concluded that a shortage of winter seed drove the population declines of most granivorous farmland birds and it probably also prevents recoveries (Gillings et al 2005;Siriwardena et al 2000Siriwardena et al , 2007. Davey et al (2010) found few clear population benefits of ES overwinter food options for granivorous species, but with multiple years per survey square, a longer survey period and more powerful analyses, we found significant positive associations between population growth rates and stubble management for threequarters of the granivorous species tested, for one or more of three spatial scales and landscape types.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of anthropogenic food is particularly important in winter, when natural sources of food are unavailable, vegetation growth having ceased and there being no insects (Moorcroft et al 2002). One of the basic sources of food in urban areas are bird-feeders, where a large number of species wintering in a town or city find their food (Siriwardena et al 2007;Jokimäki and Kaisanlahti-Jokimäki 2012); a high density of birdfeeders increases the chances of a larger number of species in an assemblage (Tryjanowski et al 2015b). However, apart from the deliberate feeding of birds at bird-feeders, the food parameter that we analysed included other sources of nourishment, such as fruit on garden trees, food laid out for domestic and other animals associated with humans and rubbish bins, all of which can provide significant sources of food during the winter (Kwit et al 2004;Bellebaum 2005).…”
Section: Discussionmentioning
confidence: 99%